Acquisition of Developmental Milestones in Hypomyelination With Atrophy of the Basal Ganglia and Cerebellum and Other TUBB4A-Related Leukoencephalopathy. (September 2021) - Gavazzi, Francesco; Charsar, Brittany A.; Williams, Catherine; Shults, Justine; Alves, Cesar A.; Adang, Laura; Vanderver, Adeline
Mutations in TUBB4A are associated with a spectrum of neurologic disorders categorized as TUBB4A -related leukoencephalopathy. Affected children can present with global developmental delay or normal early development, followed by a variable loss of skills over time. Further research is needed to characterize the factors associated with the divergent developmental trajectories in this rare monogenic disorder because this phenotypic spectrum is not fully explained by genotype alone. To characterize early psychomotor features, developmental milestones and age of disease onset were collected from medical records (n=54 individuals). Three subcohorts were identified: individuals with the common p.Asp249Asn variant vs all other genotypes with either early (<12 months of age) or late onset of presentation. Individuals with the p.Asp249Asn variant or those with non-p.Asp249Asn genotypes with later disease onset attained key milestones, including head control, sitting, and independent walking. Subjects with early-onset, non-p.Asp249Asn–associated disease were less likely to achieve developmental milestones. Next, we defined the developmental severity as the percentage of milestones attained by age 2 years. The mild form was defined as attaining at least 75% of key developmental milestones. Among cohort categorized as mild, individuals with p.Asp249Asn variant were more likely to lose acquired abilities when compared with non-p.Asp249Asn individuals. Our results suggest multiple influences on developmental trajectory, including a strong contribution from genotype and age of onset. Further studies are needed to identify additional factors that influence overall outcomes to better counsel families and to design clinical trials with appropriate clinical endpoints.